RELATION OF ELECTRONIC STRUCTURES WITH THEIR ANTIMALARIAL ACTIVITIES ON ARTEMISININ DERIVATIVES - Ria Armunanto; Sri Sudiono (Universitas Gadjah Mada, 2004)
Relation of electronic structures with their anti malaria activities on artemisinin derivatives was evaluated by means of quantitative structure activity relationship (QSAR) method. To describe electronic structures, atomic charges and dipol moments calculated by quantum mechanics on PM3 semiempirical level. A linear relation between activities and electronic structures was used to construct linear equation models. An equation model showing a good statistically criteria and a realibility of antimalarial activity was chosen to be used to design a compound with new activities against P. facilparum. Results show that 13 equation models were obtained, showing only three models with a good criteria. O2 and C4 atoms were observed for a key role of an improvement of the antimalarial activity.